Interesting presentations of mucormycosis in post-COVID patients - A., Veena H.; Bhusanoor, Manjunath; R., Bharath; Bhakthavatchalam, Supriya; Madappa, Narayanswamy (International Journal of Advances in Medicine, 2022)
Most documented cases of mucormycosis have been reported in patients with uncontrolled diabetes mellitus, neutropenia, or treatment with corticosteroids. Recently, with the second wave of COVID-19, the Indian subcontinent has witnessed a dramatic rise in mucormycosis infection in patients recovered from COVID-19. This association has been documented in various case reports/case series and institutional studies, and the mortality associated with this fungal infection is emerging as a cause of concern. Pulmonary mucormycosis is the second most common form after rhino-orbito-cerebral mucormycosis (ROCM), but most cases are diagnosed in autopsy specimens. Cutaneous, Gastro-intestinal and disseminated forms are relatively rare. This cases series comprises of 4 cases of mucormycosis in post-COVID patients with interesting presentations. We report two cases of combined pulmonary aspergillosis and pulmonary mucormycosis, one case of rhino-orbital-mucormycosis with lymph nodal involvement and one case of rhino-orbital mucormycosis with acute inflammatory demyelinating polyneuropathy (AIDP).